Russia's use of rhetoric and international law: a case study of the interconnection between legalistic language and rational choice theory - Rancāne, Elīna (Riga Graduate School of Law, 2023)
This bachelor thesis examines how Russia’s use of rhetorical language from international law allows it to maintain its strategic interests and justify its actions in the international system. Using a case study of the annexation of Crimea and the invasion of Ukraine, the thesis analyses the historical development of language in international law, the principles of state sovereignty, self-determination, and human rights, and employs rational choice theory to explain Russia’s behaviour. By utilizing language from international law, Russia is able to lend legitimacy to its actions, deflect criticism from other nations and international organizations, express its perception of international legal norms and principles, and employ lawfare. The thesis underscores the critical role of language in shaping the law and influencing the behaviour of actors in the international system, as well as the complex interplay between international law, language, and power.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Russia; Ukraine; invasion of Ukraine; the annexation of Crimea; rational choice theory